Implementasi Pembelajaran Blended Learning pada Materi PJOK Berbasis Technological Pedagogical and Content Knowledge (TPACK) pada Jenjang SMA Kelas XI terhadap Motivasi Belajar dan Hasil Belajar Siswa - Qoimuddin, Adeanto; Indahwati, Nanik; Kristiyandaru, Advendi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The digital era and technological advancements today make learning much easier. By using technology in teaching, we hope to have a positive impact on students' motivation and learning outcomes. This study implemented blended learning based on TPACK at SMA Negeri 1 Taman for 11th grade. This study used an experimental method with treatment and control groups, conducting pretests and posttests. The treatment group received blended learning based on TPACK. The results showed differences in posttest scores, explained by nonparametric Kruskal-Wallis statistical tests. While both motivation and learning outcomes had sig. > 0.05, the mean difference showed variations. The control group had a motivation mean of 48.38, whereas the treatment group scored higher at 52.62. For learning outcomes, the control group scored 8.605, while the treatment group achieved 8.614. These results indicate that the treatment group showed greater improvement. Therefore, it can be concluded that implementing blended learning based on TPACK has an impact on improving students' learning outcomes and motivation in PJOK (Physical Education, Sport, and Health). The research confirms the role of blended learning based on TPACK in enhancing students' learning outcomes in PJOK.